Reconciling agriculture with the conservation of tropical forests - Jong, W. de (Marcel Dekker, 2004)
The expansion of agriculture is widely held to be one of the causes of tropical deforestation. Simply stated, the progressive expansion of agriculture into areas of tropical forest can only occur when forests are slashed. There is little doubt that in many places an increased need for agricultural land goes hand in hand with expansion into forestland. However, the relationship between agricultural expansion and tropical deforestation is more complex than a simple addition and subtraction formula suggests. Many forms of tropical agriculture are integrated with forestry activities. Forests play an important role in the complex of resource management among many farmers in the tropics. Although such tropical agroforestry is no alternative for strict forest conservation in protected areas, it is a viable alternative—especially from a conservation point of view—to other agricultural development schemes that are often proposed or blindly copied in many tropical countries.